How to thrive as a teacher leader - Gabriel, John G. (Association for Supervision and Curriculum Development, 2020)
Organizational leadership : nurturing leadership in your school -- Strategic leadership : assembling your team -- Interpersonal leadership : communicating your leadership -- Adaptive leadership : navigating challenges and effecting change -- Motivational leadership : building climate and community -- Instructional leadership : improving student and teacher achievement